The crystal structure of 1,8-bis(4-methoxybenzoyl)naphthalene-2,7-diyl dibenzoate, C40H28O8 - Kobayashi Miyuki; Iida Kikuko; Iitsuka Hiroaki; Li Kun; Yonezawa Noriyuki; Okamoto Akiko (Zeitschrift für Kristallographie - New Crystal Structures)
C40H28O8, orthorhombic, Pna21 (no. 33), a = 27.0291(4) Å, b = 14.5593(2) Å, c = 7.95172(10) Å, V = 3129.20(7) Å3, Z = 4, R gt(F) = 0.0276, wR ref(F 2) = 0.0690, T = 193 K.